Pelatihan Pembuatan Minuman Tapache bagi Guru SMK YPPP Kabupaten Polewali Mandar - Oslan Jumadi; Andi Asmawati Azis; Nani Kurnia; Sahribulan Sahribulan; Alimuddin Ali (Jurusan Matematika FMIPA UNM, 2024)
Ananas cocomus L. (Merr), known as pineapple, is a tropical fruit quite popular throughout the archipelago, including in West Sulawesi. The use of pineapple is still limited to fresh fruit, pineapple jam, and pineapple juice produced on a household scale. One of the fermented pineapple products is a tepache drink from Mexico. Tepache is believed to contain nutrients that are useful for human health. Although there are several variations, tepache is usually made with pineapple skin, brown sugar and water; sometimes cinnamon and pepper are added. This mixture is fermented by native microorganisms from the ingredients and the environment. To expand pineapple derivative products, tepache products must be introduced to the community, including the school community. This activity aims to provide tepache making training to YPPP Wonomulyo Vocational School Teachers, Poliwali Mandar Regency, West Sulawesi Province. The implementation method used in this activity consists of 4 stages: presentation, demonstration, practice and evaluation. The activity was carried out on May 11-12, 2024, for 10 teachers. This activity has succeeded in increasing the knowledge and skills of teachers of SMK YPPP Wonomulyo, Poliwali Mandar Regency, in making kefir beverages. With this activity, teachers have learned the history, process of making and business opportunities for kefir beverages, and their application in Biology learning.